Mainan Edukasi Menggunakan Media Membantu Perkembangan Psikomotorik Anak Usia Dini - Sienny Anggraeni; Christian Anggrianto (Jurnal Vicidi, 2017)
In scientific research, entitled "USING MEDIA CAN HELP PSYCOMOTOR DEVELOMPMENT ERLY CHILDHOOD" discusses the importance of parents' role in overseeing the growth and development of children at an early age. This study will provide some basic information about the stages of child development. So that researchers can make some educational toys that can really help the psychomotor development of children at an early age. The research method that I use in this paper is a survey and study of literature. The aim of this study to determine know theories of child development and how the situation of children at age 1-3 years game is what they use, how they psycomotor development, how to behave habits of children at that age.